2022
DOI: 10.33369/consilia.5.1.77-88
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Efikasi Diri Dan Kecerdasan Emosional Dengan Prokrastinasi Akademik Siswa Dalam Pembelajaran Daring Pada Pandemi Covid-19 Di Madrasah Aliyah Negeri (Man) Kota Bengkulu

Abstract: This study aims to describe the relationship between self-efficacy and emotional intelligence with students' academic procrastination in distance learning during the covid-19 pandemic at MAN Bengkulu City. The population of this research is class XI students with a sample of 245 students taken by proportional random sampling technique. The instruments used were self-efficacy, emotional intelligence and academic procrastination questionnaires. Data analysis used multiple linear regression. The results showed (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…A frequent issue among them is academic procrastination, which refers to students' purposeful deferment in various academic activities, which is extensively impactful on their future (Wiguna et al, 2020;Pelikan et al, 2021;Tian et al, 2021;Laia et al, 2022). There has been a significant rise in academic procrastination among students (Tezer et al, 2020;Pelikan et al, 2021;Buana et al, 2022), and this phenomenon during the online learning policy is confirmed by previous studies that suggest that online learning is linked to the postponement of completing tasks related to the learning (Steel and Klingsieck, 2016). Students procrastinate although it may lead to negative consequences (Goroshit, 2018).…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…A frequent issue among them is academic procrastination, which refers to students' purposeful deferment in various academic activities, which is extensively impactful on their future (Wiguna et al, 2020;Pelikan et al, 2021;Tian et al, 2021;Laia et al, 2022). There has been a significant rise in academic procrastination among students (Tezer et al, 2020;Pelikan et al, 2021;Buana et al, 2022), and this phenomenon during the online learning policy is confirmed by previous studies that suggest that online learning is linked to the postponement of completing tasks related to the learning (Steel and Klingsieck, 2016). Students procrastinate although it may lead to negative consequences (Goroshit, 2018).…”
Section: Introductionmentioning
confidence: 70%
“…Meanwhile, previous research found that academic procrastination among state Madrasah Aliyah students in Bengkulu fell into the high category due to minimum knowledge and skills for using learning media, difficulties participating in online learning because of Internet access issues, and, in the case of delays in assignment submission, poor understanding of the materials and concepts delivered by the teacher during online learning 10.3389/feduc.2022.961820 TABLE 6 Results of regression test on the aspects of the variables. (Buana et al, 2022). This gap might be attributable to the demographic aspect related to Internet access.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Students worldwide face significant challenges with autonomous learning, computer-based learning, and a lack of interaction with classmates and teachers, therefore these necessitates lack efficient time management (Pelikan et al, 2021). The prevalence of academic procrastination among students has increased significantly (Tezer et al, 2020;Pelikan et al, 2021;Buana et al, 2022), and this phenomenon during the implementation of the online learning policy is supported by earlier research that indicates that online learning is associated with the deferral of completing tasks related to learning (Steel and Klingsieck, 2016). Although it might have unfavourable effects, students often procrastinate (Goroshit, 2018).…”
Section: Introduction "It's Like Going Into a Really Cold Lake When Y...mentioning
confidence: 99%